The market position of online fitness in the market of sports and wellness services - A. S. Putin (Путеводитель предпринимателя)
The article reveals the specifics of online fitness services, examines their position in the market of sports and wellness services. The content is determined, the cost of this type of services is estimated, as well as the consumer benefits from their acquisition.